What Katy did - Coolidge, Susan 1835-1905. (New York Garland Pub., 1976)
Twelve-year-old Katy always planned to do a great many wonderful things but in the end did something she never planned at all.
Reprint of the 1873 ed. published by Roberts Bros., Boston.
"Bibliography of her books for children": p. viii-x.
Keywords: Family life -- Fiction; Sick -- Fiction